Neural crest-derived mesenchymal progenitor cells enhance cranial allograft integration. (29th January 2021) - Glaeser, Juliane D.; Behrens, Phillip; Stefanovic, Tina; Salehi, Khosrowdad; Papalamprou, Angela; Tawackoli, Wafa; Metzger, Melodie F.; Eberlein, Samuel; Nelson, Trevor; Arabi, Yasaman; Kim, Kevin; Baloh, Robert H.; et al.
Abstract: Replacement of lost cranial bone (partly mesodermal and partly neural crest-derived) is challenging and includes the use of nonviable allografts. To revitalize allografts, bone marrow-derived mesenchymal stromal cells (mesoderm-derived BM-MSCs) have been used with limited success. We hypothesize that coating of allografts with induced neural crest cell-mesenchymal progenitor cells (iNCC-MPCs) improves implant-to-bone integration in mouse cranial defects. Human induced pluripotent stem cells were reprogramed from dermal fibroblasts, differentiated to iNCCs and then to iNCC-MPCs. BM-MSCs were used as reference. Cells were labeled with luciferase (Luc2) and characterized for MSC consensus markers expression, differentiation, and risk of cellular transformation. A calvarial defect was created in non-obese diabetic/severe combined immunodeficiency (NOD/SCID) mice and allografts were implanted, with or without cell coating. Bioluminescence imaging (BLI), microcomputed tomography (μCT), histology, immunofluorescence, and biomechanical tests were performed. Characterization of iNCC-MPC-Luc2 vs BM-MSC-Luc2 showed no difference in MSC markers expression and differentiation in vitro. In vivo, BLI indicated survival of both cell types for at least 8 weeks. At week 8, μCT analysis showed enhanced structural parameters in the iNCC-MPC-Luc2 group and increased bone volume in the BM-MSC-Luc2 group compared to controls. Histology demonstrated improved integration of iNCC-MPC-Luc2 allografts compared to BM-MSC-Luc2 group and controls. Human osteocalcin and collagen type 1 were detected at the allograft-host interphase in cell-seeded groups. The iNCC-MPC-Luc2 group also demonstrated improved biomechanical properties compared to BM-MSC-Luc2 implants and cell-free controls. Our results show an improved integration of iNCC-MPC-Luc2-coated allografts compared to BM-MSC-Luc2 and controls, suggesting the use of iNCC-MPCs as potential cell source for cranial bone repair. Abstract : Bone marrow-derived mesenchymal stromal cells (BM-MSCs) were obtained from human bone marrow. Induced neural crest cell-mesenchymal progenitor cells (iNCC-MPCs) were generated from induced pluripotent stem cell-derived iNCCs. Cells were luciferase transfected and seeded onto decellularized allografts, which were implanted into 5 mm circular calvarial defects in non-obese diabetic/severe combined immunodeficiency (NOD/SCID) mice. Allograft only was used as controls. Mice were followed for a duration of 8 weeks. Cell survival, allograft integration, and tissue morphology and transplanted cell contribution were monitored via bioluminescence imaging (BLI), micro-computed tomography (μCT), and histology and immunofluorescence (IF). Green arrow: BLI; yellow arrow: μCT; Orange arrow: histology and IF; Blue arrow: biomechanical test.